Model Pembelajaran 4-D Thiagarajan: Studi Teoritis dan Aplikasinya dalam Pengembangan Alat Pembelajaran - Iffatul Aimmah; Madhar Amin (Journal of Public Policy Analys, 2025)
Learning tools that are developed through a systematic approach are key in creating effective and competency-oriented learning. The 4-D model developed by Thiagarajan, Semmel, and Semmel offers a framework for developing teaching tools through four stages: Define, Design, Develop, and Disseminate. This study aims to examine the characteristics and application of the 4-D model stages in learning development in the contemporary era. The method used is a literature study with a descriptive-qualitative approach, through a review of journals, books, and related scientific documents. The results show that in the Define stage, this model emphasizes needs analysis, student characteristics, and learning objectives. The Design stage focuses on media selection, test preparation, and teaching format design. Furthermore, the Develop stage involves expert validation and pilot testing, while the Disseminate stage includes strategies for disseminating the device to users. These four stages form a structured and adaptive process to the demands of 21st century learning.